Advances in intellectual capital performance measurement: a state-of-the-art review. Issue 2 (30th May 2019) - Lee, Cheng Sheng; Wong, Kuan Yew
Abstract : Purpose: The purpose of this paper is to present a review on the latest developments, approaches and methods in intellectual capital (IC) performance measurement. Design/methodology/approach: A total of 53 research papers from high-ranking journals concerning the advances in IC performance measurement were thoroughly reviewed and classified to identify the advanced approaches and methods that have been used to evaluate IC performance. Findings: It is clear that the current application of advanced or intelligent methods in IC performance measurement is still at the primary stage. The reviewed approaches mainly focus on two core applications. First is to assist the data collection or data handling process and second is to enhance the result computation process to obtain a more reliable and realistic value that represents the performance of IC. Research limitations/implications: This study offers a foundation and guideline for the researchers who wish to integrate advanced methods into IC performance measurement based on the reviewed advanced approaches in terms of their respective functions, strengths and limitations. It stimulates the creation of new IC performance measurement models that use advanced approaches to cope with real-life problems and dynamic conditions. Originality/value: This paper contributes to the literature on IC performance measurement, in light of advances in technology. In general, five advanced approaches were identified, analyzed and discussed. Future research directions were presented to provide new insights for researchers to apply advanced methods in IC performance measurement, together with theoretical and managerial implications.